KOMUNIKASI PERSUASIF HUMAS PARIWISATA PURA MANGKUNEGARAN SURAKARTA DALAM MENINGKATKAN PENGUNJUNG - Nabila, Shandra; Suryo, Herning; Kusumo Aji, Haryo (Solidaritas, 2025)
Persuasive communication is communication that involves persuading and persuading which aims to change a person's attitude, opinion, or behavior. In this process, the communicator can plan to influence the communicant. The purpose of this study is to determine the persuasive communication of the Pura Mangkunegaran Tourism Public Relations in increasing visitors. The type of research used is a qualitative descriptive research method. The focus of the research in this study is how the persuasive communication of the Pura Mangkunegaran tourism public relations uses persuasive communication techniques, namely association techniques, integration techniques, reward techniques, arrangement techniques and red-herring techniques. Data collection techniques used are observation, interviews and documentation. In this study, the researcher used the Pura Mangkunegaran tourism public relations and Pura Mangkunegaran tourism visitors as sources. The data analysis technique used is interactive model data analysis developed by Miles and Huberman. The results of the research on persuasive communication of Pura Mangkunegaran tourism public relations in increasing visitors using persuasive communication techniques l, namely association techniques, integration techniques, reward techniques, arrangement techniques and red-herring techniques show that Pura Mangkunegaran tourism public relations uses social media which is a channel used by communication paths to convey messages from Pura Mangkunegaran tourism public relations to the community and potential local and foreign tourists. This study concludes that persuasive communication carried out by Pura Mangkunegaran tourism public relations contributes significantly to increasing the number of visitors. However, further innovation is needed in communication strategies, especially in utilizing digital technology to reach a wider audience. Keywords: Persuasive Communication, Public Relations, Mangkunegaran Palace Tourism